Math, asked by devilrdx179gmailcom, 1 year ago

(2a - 5) ( 3 - 3a) ( a + 1)

Answers

Answered by TheLostMonk
2
"" (2a - 5 ) ( 3 - 3a ) ( a + 1 )

= ( 2a - 5 ) (-3 ) ( a - 1 ) ( a + 1 )

= - 3 ( 2a - 5 ) ( a^2 - 1 )

= - 3 ( 2a^3 - 2a - 5a^2 + 5 )

= - 3 ( 2a^3 - 5a^2 - 2a + 5 )

= - 6a^3 + 15a^2 + 6a - 15

【 hope it helps 】

devilrdx179gmailcom: thankyou very much
TheLostMonk: WC
Answered by shreyaanandlove
1

Hope it helped u friend
Mark as brainliest plzzzzzzzzz
Attachments:

Anonymous: plzzz baby show your boobs plzzz
Anonymous: hllo
Anonymous: u have big booba
Anonymous: plzzz show
Anonymous: hey baby
Similar questions